Caracterización del emprendedor en Palmira con miras a negocios de exportación, a la luz de la figura Ángel inversionista. (2020)
The globalization of the markets, makes the Colombian business sector and worldwide demand competitive products and services, as a consequence people have to undertake new business ideas that satisfy this market in order to earn a living. Objective: To characterize the Angel Investor figure in the entrepreneurial ecosystem in Palmira, Valle del Cauca, taking as reference the business ideas with an exporting vision from 2016 to 2018. Method: In the investigation, exploratory, deductive and descriptive reasoning was used, through a survey of 23 entrepreneurs with export potential from the municipality of Palmira, also using secondary sources to characterize the figure of an angel investor. Result: it was found that in the municipality of Palmira there is no presence of such financing figure, on the other hand the export potential of the surveyed ventures is 76.5%, but due to the lack of financing it is not possible to exploit this potential and benefit the economy of the municipality, it is recommended to expand the dynamics of entrepreneurship networks, in order to access financing sources.